Accurate Targeting in the Indonesia Hopeful Family Program (Pkh) at Koto Tangah Sub-District, Padang City - Haryati, Riri; Suasti, Yurni (Sumatra Journal of Disaster, Geography and Geography Education, 2022)
This study discussedthe program’s targeting accuracy in the Hopeful Family Program at sub-district of Koto Tangah, Padang City consisting of poverty criteria according to Statistics Indonesia, the knowledge of Social Registry, and components of Hopeful Family Program. This study used mixed methods research and the present study found 9 of 14 criteria set byStatistics Indonesia were not fulfilled by beneficiary familiesof Hopeful Family Program in sub-district Koto Tangahcategorized as poor people. Only 2 of 14 criteria were met as the 8th criterion regarding to consumejust meat/milk/chicken once a weekand the 9th criterion regarding to buy just one set of new clothes a year. The remaining 12 criteria were not on target with a range of 63.4% to 100%.The inaccuracy of beneficiary families targeting occurred because some poverty criteria items were no longer relevant according to statistics Indonesia, outdated data of social registry, and administrative disorder by people.